2020
DOI: 10.1136/bmjopen-2020-041121
|View full text |Cite
|
Sign up to set email alerts
|

Does tension applied in kinesio taping affect pain or function in older women with knee osteoarthritis? A randomised controlled trial

Abstract: ObjectiveTo analyse the short-term effects of kinesio taping (KT) with tension (KTT) or without tension (KTNT) in older women with knee osteoarthritis (KOA), and compare them to controls who did not receive KT.DesignRandomised controlled trial.SettingUniversity physiotherapy school clinic.ParticipantsForty-five older women (fifteen participants per group) with 66.8 (±5.6) years and clinical diagnosis of KOA were assessed pre, post and 3 days after intervention.InterventionsParticipants were randomly allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…Two other studies evaluating the effects of KT on pain and functionality in knee osteoarthritis also reported that there were no statistically significant effects of KT application on any parameter. 12,22 In our study, an additional benefit of KT to exercises was not shown in patients with knee osteoarthritis in terms of pain and functionality.…”
Section: Variablescontrasting
confidence: 52%
“…Two other studies evaluating the effects of KT on pain and functionality in knee osteoarthritis also reported that there were no statistically significant effects of KT application on any parameter. 12,22 In our study, an additional benefit of KT to exercises was not shown in patients with knee osteoarthritis in terms of pain and functionality.…”
Section: Variablescontrasting
confidence: 52%
“…Pinherio et al 27 concluded that the change in the WOMAC results of a single session of kinesiology taping applied to knee OA patients in the intervention group was not different from the placebo group. We also obtained a similar result for WOMAC pain and function in our study.…”
Section: Discussionmentioning
confidence: 99%